Sinergi Kepemimpinan Transformasional dan Servant Leadership dalam Pengembangan Sekolah Berbasis Pesantren di SMP Terpadu Darul Falah Malang - Ahmad Muhlisin; Sinollah (Jurnal Bisnis Islam dan Kewirausahaan, 2026)
This research was motivated by the condition of Darul Falah Islamic Boarding School in Malang, which experienced a period of stagnation after the passing of its caregiver, resulting in the absence of resident students. Significant changes emerged following the establishment of a formal junior high school within the institution. The leadership style of the new principal attracted researchers’ attention because it successfully encouraged institutional transformation and development. This study focuses on examining the implementation and influence of the synergy between transformational and servant leadership characteristics in realizing a quality Islamic boarding school-based school at Darul Falah Integrated Junior High School Malang. The study aims to describe how transformational-servant leadership is implemented and how it contributes to improving the quality of the institution. This research employs a descriptive qualitative approach. Data were collected through observations, interviews, and documentation. The research subjects consisted of the principal, the Islamic boarding school caregiver, teachers, students, and parents. The findings indicate that leadership in Islamic boarding school-based educational institutions can effectively integrate transformational and servant leadership characteristics. Through this synergy, leaders are able to inspire change, serve the educational community, strengthen collaboration, and encourage sustainable institutional development, thereby improving the quality and competitiveness of the school.